Phytomass and quality of yellow passion fruit seedlings under salt stress and silicon fertilization - Diniz, Genilson Lima; Nobre, Reginaldo Gomes; Lima, Geovani Soares de; Souza, Leandro de Pádua; Soares, Lauriane Almeida dos Anjos; Gheyi, Hans Raj (Comunicata Scientiae, 2020)
The semiarid region of Northeastern Brazil is characterized by long drought periods, and the use of saline waters appears as an alternative for the expansion of irrigated areas. Associated with the use of these waters, silicon fertilization constitutes an important attenuator of salt stress. In this perspective, this study aimed to evaluate the phytomass production and quality of the passion fruit cultivar ‘Gigante Amarelo’ grown with saline water and silicon fertilization. The experiment was conducted in a plant nursery belonging to the Center of Agrifood Science and Technology, in the municipality of Pombal-PB. A completely randomized block design in a 5 x 5 factorial scheme was used, referring to five levels of electrical conductivity of the irrigation water (0.3, 1.0, 1.7, 2.4, and 3.1 dS m-1) and five doses of silicon fertilization (0; 25; 50; 75, and 100 g of potassium silicate/plant), with four replications and two plants per plot. The phytomass accumulation (leaves, stem, and roots), as well as the total dry phytomass, shoot dry phytomass, root/shoot ratio, and the quality index of Dickson were evaluated. The data obtained were subjected to the F-test at 0.01 and 0.05 level of probability. The electrical conductivity of water from 0.3 dS m-1 caused the decrease of phytomass production in seedlings of the passion fruit cultivar ‘Gigante Amarelo’, although it is possible to produce good quality passion fruit seedlings with water salinity up to 3.1 dS m-1. The doses of silicon fertilization mitigated the effect of salt stress on the root/shoot ratio of plants of the passion fruit cultivar ‘Gigante Amarelo’.